2015
DOI: 10.1155/2015/743086
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Method for Thermal Instability of Nonlinearly Charged BTZ Black Holes

Abstract: We consider three-dimensional BTZ black holes with three models of nonlinear electrodynamics as source. Calculating heat capacity, we study the stability and phase transitions of these black holes. We show that Maxwell, logarithmic, and exponential theories yield only type one phase transition which is related to the root(s) of heat capacity, whereas, for correction form of nonlinear electrodynamics, heat capacity contains two roots and one divergence point. Next, we use geometrical approach for studying class… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 97 publications
1
65
0
Order By: Relevance
“…Depending on the choice of the thermodynamical potential, the components of the phase space differ (this is due to the fact that each thermodynamical quantity has its specific extensive parameters). There are several well-known methods for constructing a phase space; see Weinhold [76,77], Ruppeiner [78,79], Quevedo [81,82], and HPEM [83][84][85][86]. In order to investigate the thermodynamical properties of the system, the successful method has divergencies which exactly are matched with bound and phase transition points.…”
Section: Geometrical Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the choice of the thermodynamical potential, the components of the phase space differ (this is due to the fact that each thermodynamical quantity has its specific extensive parameters). There are several well-known methods for constructing a phase space; see Weinhold [76,77], Ruppeiner [78,79], Quevedo [81,82], and HPEM [83][84][85][86]. In order to investigate the thermodynamical properties of the system, the successful method has divergencies which exactly are matched with bound and phase transition points.…”
Section: Geometrical Thermodynamicsmentioning
confidence: 99%
“…Therefore, in order to remove these problems, a new method was proposed in Refs. [83][84][85][86] which is known as the HPEM (Hendi-Panahiyan-Eslam Panah-Momennia) metric. In this paper, we want to study the thermal stability and phase transition in the context of the methods of GT and extended phase space for black holes in Einstein gravity with the PMI source in higher dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the context of the GTs approaches for the black hole thermodynamics have shown that the Ricci scalars of Weinhold, Ruppeiner and Quevedo metrics may lead to extra divergencies which are not matched with the bound points and the phase transitions [97][98][99][100]. In other words, there were cases of mismatch between divergencies of the Ricci scalar and the mentioned points (bound and phase transition points), and also existence of extra divergency unrelated to these points were reported [97][98][99][100]. In order to overcome the shortcomings of the mentioned methods (Weinhold, Ruppeiner and Quevedo metrics), the HPEM method was introduced and it was shown that the specific structure of this metric provides satisfactory results regarding GTs of different classes of the black holes.…”
Section: Geometrical Thermodynamicsmentioning
confidence: 99%
“…[97][98][99][100], for more details). In other words, obtained results of these three approaches were not consistent with those extracted from other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although Quevedo could solve some problems which previous metrics were involved with, it has been confronted with another problems in some specific systems. To solve these problems, a new method was proposed in [85][86][87] which is known as HPEM metric. It was shown that HPEM metric is completely consistent with the results of the heat capacity in canonical ensemble in different gravitational systems.…”
Section: Introductionmentioning
confidence: 99%